Pengembangan Promosi Desa Cibubuan melalui Pembuatan Profil Website yang Interaktif - Rohmanto, Ricky; Aprilianti, Putri; Resmala, Luthpia R.; Parid, Miftahul Parid (Ma'soem University, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) is one of the forms of student dedication to society that focuses on applying academic knowledge for community development. In the KKN program conducted in Cibubuan Village, a team of students from Ma’soem University carried out a digital transformation activity through the design and implementation of an interactive village profile website as a medium for information and promotion of local potential. The purpose of this activity is to provide a digital platform that can be widely accessed so that the village’s local potentials can be recognized at both national and global levels. The implementation method used the Asset-Based Community Development (ABCD) approach, which focuses on mapping local assets, collaborating with village officials, and redeveloping the Webdesa into a more interactive and informative platform. The results show that the implemented website serves as an effective medium for publishing village profiles, community activities, and promoting local small enterprises (UMKM). The presence of this interactive profile website strengthens the village’s digital identity, expands the reach of local potential promotion, and enhances transparency and community participation in village information management.